The relationship of wearing a wetsuit in long-distance open-water swimming with sex, age, calendar year, performance, and nationality – crossing the “Strait of Gibraltar” - Nikolaidis PT; Sousa CV; Knechtle B (Dove Medical Press, 2018)
Pantelis Theodoros Nikolaidis,1 Caio Victor Sousa,2 Beat Knechtle3,4 1Exercise Physiology Laboratory, Nikaia, Greece; 2Graduate Program in Physical Education, Catholic University of Brasília, Brasília, Brazil; 3Medbase St. Gallen Am Vadianplatz, St. Gallen, Switzerland; 4Institute of Primary Care, University of Zurich, Zurich, Switzerland Aim: The aim of the present study was to investigate the relationship of wearing a wetsuit with sex, age group, nationality, calendar year, and performance in crossing the “Strait of Gibraltar”(14.3 km). Materials and methods: A sample of 1,130 open-water (females, n=180, age 35.9±11.9 years; males, n=950, age 40.0±10.2 years) ultra-distance swimmers crossing the “Strait of Gibraltar” since 1950 was analyzed. Results: Male, older, and Spanish swimmers used wetsuits more often than female, younger, and athletes of other nationalities, respectively, and the use of the wetsuit has increased during the past three decades. Swimmers with wetsuits were faster than those without. Male athletes aged 30–34 years were faster than athletes >60 years. Female athletes were younger than male athletes, and swimmers with wetsuits were older than those without. The Spanish were faster than the American swimmers and athletes from other nationalities, and the American swimmers were the oldest. Conclusion: In summary, swimmers were faster when using a wetsuit, and local Spanish swimmers were the fastest and also used wetsuits most frequently. Male and older swimmers used wetsuits more often than other swimmers, and the use of wetsuits has increased in the last three decades. Keywords: aging, master athlete, endurance, water sport, physiology, gender